Proceeding of the Second International Conference on Microelectronics, Computing & Communication Systems (MCCS 2017) - Nath, Vijay; Mandal, Jyotsna Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The volume presents high quality papers presented at the Second International Conference on Microelectronics, Computing & Communication Systems (MCCS 2017). The book discusses recent trends in technology and advancement in MEMS and nanoelectronics, wireless communications, optical communication, instrumentation, signal processing, image processing, bioengineering, green energy, hybrid vehicles, environmental science, weather forecasting, cloud computing, renewable energy, RFID, CMOS sensors, actuators, transducers, telemetry systems, embedded systems, and sensor network applications. It includes original papers based on original theoretical, practical, experimental, simulations, development, application, measurement, and testing. The applications and solutions discussed in the book will serve as a good reference material for future works.
Preface -- Acknowledgements -- About the Editors -- Table of Contents -- 66 papers -- Author Index.
Keywords: Electronics; Signal processing; Renewable energy sources; Electronics and Microelectronics, Instrumentation; Signal, Speech and Image Processing; Renewable Energy